The impacts of work environment, mentorship, technological integration, and employee turnover on TVET students' intention toward career in the hospitality and tourism sector: a quantitative analysis / Jeffridzal Ismail, Mohd Salehuddin Mohd Zahari and Chemah Thamby Chik - Ismail, Jeffridzal; Mohd Zahari, Mohd Salehuddin; Thamby Chik, Chemah (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2024)
This study explores the impact of various factors, including the working environment, mentoring, staff turnover, and technology application, on the career intentions of Technical and Vocational Education and Training (TVET) students within the hospitality and tourism industry. Employing a quantitative research methodology and a purposive sampling approach, the study successfully collected and analyzed 322 valid questionnaires, utilizing inferential statistics for data analysis. The study's findings reveal that, during their industrial training experiences, TVET students exhibit a positive perception of the working environment prevalent in the hospitality and tourism industry. Additionally, industry mentors play a crucial role in reinforcing their interest in this sector, while the integration of technology in the workplace is viewed favorably and significantly contributes to their intentions to pursue careers in the hospitality and tourism industry. Notably, staff turnover observed by TVET students during their internship programs does not appear to have a substantial influence on their career intentions. These insightful findings carry significant implications for a variety of stakeholders, including TVET students, Polytechnic institutions, and the broader hospitality and tourism industry.